Incidence of orange spotting and characterization of coconut cadang-cadang viroid variants in Selangor and Sabah oil palm plantations, Malaysia - Cheong, Li Chu (2012)
Orange Spotting (OS) is a disorder of oil palm (Elaeis guineensis Jacq.) that has been associated with coconut cadang-cadang viroid (CCCVd), where CCCVd variants characterized from oil palms had more than 90% sequence similarity with CCCVd in coconut. These CCCVd oil palm variants pose a threat to the oil palm industry in Malaysia because CCCVd has caused extensive losses to coconut production in the Philippines. Routine screening and detection methods for CCCVd are radioactive based methods, which are expensive and hazardous. In view of this, the objectives of this study are (a) to survey for OS incidence in Selangor and Sabah oil palm plantations and to sequence the CCCVd variants in oil palm, (b) to develop a non-radioactive RPA using DIG-labelled probe for detection of CCCVd variants in oil palm. Preliminary survey of OS incidence was done in Sabah (Papar and Tawau areas) and Selangor (Kuala Selangor area) from 2009 until 2010 by symptom observation. A minimum of 500 palms were randomly observed from the study plots for the assessment of disease incidence (DI) and disease severity. The visual observation was then supported by molecular analysis and sequence characterization. Regarding to the experiment results from molecular diagnosis, palms with OS mild (1-30%) were excluded from the measurement of incidence. Therefore, OS incidence in Sabah ranged from 13-17% of total surveyed palms, while in Selangor the OS incidence was slightly higher at 25%. This is the first report survey of OS incidence conducted in commercial oil palm plantations in Selangor and Sabah. The surveys do not reflect actual OS incidence rate of an entire estate or plantation due to the limited number of palms surveyed. Larger scale field survey in oil palm plantations in Malaysia is recommended for future research together with a consistent OS monitoring system in order to quantify the actual OS incidence. Of total 27 tested palms, approximately 48% of palms presented positive signal to CCCVd on molecular diagnosis using dot blot assay and about 19% of tested palms were characterized and sequenced. A new oil palm CCCVd variant (OP252-SBK88 and OP252-SBTW122) was discovered in Sabah that is being reported for the first time compared to those CCCVd variants reported from previous studies in Malaysian oil palm showed over 95% sequence similarity to the 246 nucleotides form of CCCVd in coconut palm. Non-radioactive RPA using digoxigenin (DIG)- labelled CCCVd full length cRNA probes was developed for detection of CCCVd from oil palm with OS moderate and severe symptoms. Two out of four selected positive palms from dot blot screening (OPSBK88 and OPSBTW122 from Sabah) were detected positive for CCCVd variants, produced three protected fragments approximately 175, 125 and 50 nucleotides after RNAse digestion similar to the positive control (OPSRD6). In this study, the sensitivity of DIG-labelled RPA was lesser compared to the previous study with radioactive-based detection; however, all of the practical advantages of non-radioactive RPA were over radioactivity in term of cost and time consuming, labor intensive, handling safety and environmental health.